Election Data Transparency: Obtaining Precinct-Level Election Returns. (4th March 2022) - Willis, Derek; Merivaki, Thessalia; Ziogas, Ioannis
Abstract : Election data transparency, accessibility, and usability constitute key dimensions of electoral integrity, as they allow for an additional accountability check on how states and localities run elections. Yet, it is an understudied topic, because of challenges in systematic data collection. Lack of data transparency has important implications for a democratic election process: It can reflect non-compliance with federal and state election laws, discriminatory practices, or lack of capacity in modernizing the conduct of elections. Thus far, there is no standard way for states to report election data, and there is no standard way to request, collect, and disseminate them. This paper presents the various ways state and local governments make official precinct-level election results publicly available, based on an OpenElections collection effort that covered primary and general elections in 2016 and 2018 in every U.S. state. We describe methods for obtaining official precinct results, ranging from formal records requests under state law, photographing pages in-person, to results sent by fax, and the benefits and costs of those methods. Using this information, local and state officials could adopt processes and policies to promote public access to official precinct-level election results.